2022
DOI: 10.1021/acs.jafc.2c00776
|View full text |Cite
|
Sign up to set email alerts
|

The Vital Role of ShTHIC from the Endophyte OsiSh-2 in Thiamine Biosynthesis and Blast Resistance in the OsiSh-2-Rice Symbiont

Abstract: Endophytes can benefit the growth and stress resistance of host plants by secreting bioactive components. Thiamine is an essential vitamin involved in many metabolic pathways and can only be synthesized by microbes and plants. In this study, we found that thiamine could inhibit the development of the phytopathogen Magnaporthe oryzae and decrease the rice blast index under field conditions. In the thiamine biosynthesis pathway, the key enzyme ShTHIC of an endophyte Streptomyces hygroscopicus OsiSh-2 and OsTHIC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…For M. oryzae punch inoculation assays. Rice leaf inoculation assays were performed following a previously described method 68 . Briefly, detached leaves of four-week-old rice were lightly wounded with a mouse ear punch, and then 6 μl of M. oryzae spore suspension (concentration of 5 × 10 5 conidia/mL in 0.02% Tween-20) was applied to the wounded leaves.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For M. oryzae punch inoculation assays. Rice leaf inoculation assays were performed following a previously described method 68 . Briefly, detached leaves of four-week-old rice were lightly wounded with a mouse ear punch, and then 6 μl of M. oryzae spore suspension (concentration of 5 × 10 5 conidia/mL in 0.02% Tween-20) was applied to the wounded leaves.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the antagonism of OsiSh-2 (WT) and Δ cchH against M. oryzae , a dual-culture assay was performed 68 . Briefly, M. oryzae was inoculated in the centre of the PDA plate, and the strains were streaked one line 30 mm above the centre.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we found that the rice endophyte Streptomyces hygroscopicus OsiSh-2 and its cell-free culture filtrate (CFC) had strong antagonistic activity against M. oryzae via the action of nigericin and siderophores ( 3 , 29 ). OsiSh-2 could regulate thiamine biosynthesis and thus assist in blast resistance in the OsiSh-2-rice symbiont ( 30 ). Specifically, OsiSh-2 also has ISR activity in rice for resisting M. oryzae , including induction of a priming response ( 31 ).…”
Section: Introductionmentioning
confidence: 99%